The leadership challenge : how to make extraordinary things happen in organizations - Kouzes, James M., 1945-; Posner, Barry Z. (San Francisco, CA : Jossey-Bass, 2012)
The Leadership Challenge, based on Kouzes and Posner's research, this edition casts their work in context for today's world, proving how leadership is a relationship that must be nurtured and can be learned. Features over 100 all-new case studies and examples, which show The Five Practices of Exemplary Leadership in action around the world. Focuses on toughest organizational challenges leaders face today. Addresses changes in how people work and what people want from their work.
Introduction: Making extraordinary things happen in organizations -- When leaders are at their best -- Clarify values -- Set the example -- Envision the future -- Enlist others -- Search for opportunities -- Experiment and take risks -- Foster collaboration -- Strengthen others -- Recognize contributions -- Celebrate the values and victories -- Leadership is everyone's business.
Includes bibliographical references (pages 347-374) and index.
Keywords: Leadership; Executive ability; Management -- Case studies; Leadership; Personnel Management; Professional Competence; Executive ability; Leadership; Management; Personnel Management; Professional Competence; Case studies